On τ-Closed Formations of n-Ary Group - Al-Dababseh, Avni Faez (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We prove that if G is a nonsingle-element n-ary finite group that belongs to a τ-closed formation \(\mathfrak{F}\) , then \(G/{\text{soc(}}G{\text{)}} \in Φ _τ (\mathfrak{F})\) , where \(Φ _τ (\mathfrak{F})\) is the intersection of all maximal τ-closed subformations of the τ-closed formation of n-ary groups \(\mathfrak{F}\) .